Technical Aspects of Telepathology with Emphasis on Future Development - P. Schwarzmann; B. Binder; R. Klose (Analytical Cellular Pathology)
Pathology undergoes presently changes due to new developments in diagnostic opportunities and cost saving efforts in health care. Out of the wide field of telepathology the paper selects three prototype applications: telepathology in teleeducation, expert advice for preselected details of a slide and finally telepathology for remote diagnosis. The most challenging field for remote diagnosis is the application in the frozen section scenario. The paper starts with the mental experiment to map conventional procedures to counterparts in telepathology.